Tantangan Pemberian Kewenangan Bagi Penyidik Pejabat Pegawai Negeri Sipil (PPNS) Kehutanan Sumatera Barat Pada Tindak Pidana Pencucian Uang - Annisa'un Rasyiqah (Fakultas Hukum Universitas Andalas, 2023)
Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering (AML Law) serves as the cornerstone of anti-money laundering enforcement in Indonesia today, but it still falls short in accommodating the needs of money laundering law enforcement. Explanation of Article 74 of the AML Law limits the role of criminal investigators solely to the National Narcotics Agency (BNN), the Corruption Eradication Commission (KPK), the Police, the Prosecutor's Office, Customs, and Tax Authorities. This explanation of Article 74 contradicts the AML Law. This situation leaves the Environmental and Forestry Crime Investigators (PPNS Kehutanan) without the authority to investigate money laundering cases in the forestry sector and hampers efforts to combat money laundering. Ultimately, Constitutional Court Decision No. 15/PUU-XIX/2021 breathed new life into money laundering investigations by broadening the definition of investigators and granting authority to PPNS Kehutanan to handle money laundering cases. Based on this research, the author concludes that following Constitutional Court Decision No. 15/PUU-XIX/2021, PPNS in the forestry sector has the authority to investigate cases of money laundering. The authority held by PPNS Kehutanan in conducting money laundering investigations includes the power to delay transactions, the power to request information about wealth from the reporter, the power to seize assets, and the power to block assets. In West Sumatra, the investigation of money laundering in the forestry sector is assigned to PPNS of the Provincial Forestry Service and PPNS of the Directorate General of Law Enforcement and Forest Protection (Gakkum LHK). These two institutions coordinate to handle all forestry crimes, including money laundering. Furthermore, coordination is also carried out with the National Police (POLRI) and the Financial Transaction Reports and Analysis Center (PPATK) in resolving money laundering cases.